SYSTEM-STRUCTURAL MODELING OF TECHNOLOGICAL PROCESSES FOR MANUFACTURING «COVER»-TYPE PARTS - Кушніров, Павло; Лобов, Сергій; Дворніченко, Сергій (SWorldJournal, 2025)
This paper discusses the methodology of system-structural modeling of technological processes and systems using the example of a «cover»-type part. The principles of the systems approach were applied in the analysis of mechanical assembly production. The